Evaluation of Morinda tomentosa accession under zero irrigation conditions of semi-arid ecosystem (Indian Journal of Arid Horticulture, 2013)
Morinda sp. belongs to family Rubiaceae and the about particular genotype was selected. A total of sixteen  plant is believed to have originated in India and South East fruits were randomly collected from all the direction of each  Asia and to be precise in Andaman and Nicobar Islands genotype to record the qualitative and quantitative (Singh, 2009). It is also known by different vernacular morphological characters. The extent of variation in  names in different parts of world like nuna, ach, Indian physico-chemical traits of fruits from different location was  mulberry, awl, great Morinda, cheese fruit, mouse's recorded. Atotal of 20 genotypes were collected which had  pineapple, jumbie breadfruit, hog apple, pain killer, fairly wide spectrum of variability with respect to growth,  mengkudu, aledi and bilimbi. It is grown wildly in many flowering, fruiting behaviour and quality attributes. The  places throughout India viz. Madhya Pradesh, Gujarat, samples of leaf, bud, flower and fruit were brought to the  Rajasthan, Andhra Pradesh etc. It is hardy green small tree laboratory for morphological study and fruit quality  bearing flowers and fruits throughout the year under attributes. The observations on qualitative characteristics  different agro-climatic conditions, but more prominently like tree habit, and leaf morphology were recorded visually.  during rainy season (April to August). Plants of different Observation on the leaf morphology was in terms of leaf  species of Morinda spp. are found to be growing in fragile shape, leaf apex, leaf margin and leaf colour was taken as  edephoclimatic conditions and adapted to acidic, alkaline illustrated by Wilde et al., 1972 and Simpson, 2006.
Keywords: morphological; illustrated; pineapple